VmMon1-Ccz1 Complex Is Required for Conidiation, Autophagy, and Virulence in Valsa mali - Liangsheng Xu; Xiaolong Zhang; Dian Zheng; Yali Chang; Feiran Zhang; Yinghao Wang; Lili Huang (Molecular Plant-Microbe Interactions, 2022)
Apple Valsa canker caused by Valsa mali is a serious disease in eastern Asia, especially in China. In our previous proteomics study, monensin sensitivity 1 protein in Valsa mali (VmMon1) was identified to be significantly upregulated during V. mali infection. It was reported Mon1 protein formed a heterodimer called MC (Mon1-Ccz1) complex with caffeine, calcium, and zinc sensitivity 1 protein (Ccz1) in yeast. However, Ccz1 had not been identified in plant-pathogenic fungi such as Fusarium graminearum and Magnaporthe oryzae. Here, we identified a Ccz1 ortholog VmCcz1 in V. mali, by using DELTA-BLAST. The interaction of VmMon1 and VmCcz1 were verified using yeast two-hybrid assay, bimolecular fluorescence complementation, and co-immunoprecipitation assays. Further yeast three-hybrid screenings determined that VmRab7 (Ras-related protein in V. mali) interacted with the MC complex. Targeted gene deletion showed that the ∆VmMon1 and ∆VmCcz1 mutants were defective in vegetative growth, conidiation, and pathogenicity. In addition, both mutants were more sensitive to osmotic and oxidative stresses and intracellular protein transport inhibitors. Cytological examination revealed that the ∆VmMon1 and ∆VmCcz1 mutants were impaired in vacuole fusion and autophagy. More importantly, expression of pectinase genes decreased in both mutants compared with those of the wild type during infection. Overall, our study identified Mon1 and Ccz1 genes in V. mali and provided evidence that VmMon1 and VmCcz1 are critical components that modulate vacuole fusion and autophagy, thereby affecting the development, conidiation, and pathogenicity of V. mali. [Graphic: see text] Copyright © 2022 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.